2019
DOI: 10.20944/preprints201908.0218.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospective and Prospective Look at Aflatoxin Research and Development from a Practical Standpoint

Abstract: Among the array of structurally and toxicologically diverse mycotoxins, aflatoxins have attracted the most interest of scientific research due to their high toxicity and incidence in foods and feeds. Despite the undeniable progress made in various aspects related to aflatoxins, the ultimate goal consisting of reducing the associated public health risks worldwide is far from being reached due to multiplicity of social, political, economic, geographic, climatic, and development factors. However, a reasonable deg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Most importantly, they can invert to their highly toxic precursors in foods or after ingestion [27]. For example, aflatoxicol, which is 25 to 50% as potent as its parent AFB1, is almost entirely converted back in the liver to either the more toxic parent AFB1 or to AFM1 [1,[165][166].…”
Section: Toxicity Of Aflatoxins and Major Aflatoxicosis Outbreaksmentioning
confidence: 99%
See 3 more Smart Citations
“…Most importantly, they can invert to their highly toxic precursors in foods or after ingestion [27]. For example, aflatoxicol, which is 25 to 50% as potent as its parent AFB1, is almost entirely converted back in the liver to either the more toxic parent AFB1 or to AFM1 [1,[165][166].…”
Section: Toxicity Of Aflatoxins and Major Aflatoxicosis Outbreaksmentioning
confidence: 99%
“…This assumption has been debated since some authors suggested that aflatoxins have a threshold response [194] which, if confirmed, will change drastically the current perception of aflatoxin risks and urge the revision of previous assessments on a new basis using specifically adapted mathematical models and approaches. In addition, due to the high uncertainties and inaccuracies in dietary intake estimations, there is a tendency to use biomarkers for exposure determinations; yet, the ideal biomarker is still lacking for this purpose, as was discussed earlier [1]. Presently, the biomarker aflatoxin-Lys adduct appears to be the best candidate to estimate chronic exposure.…”
Section: Risk Assessment Of Aflatoxin Dietary Intakementioning
confidence: 99%
See 2 more Smart Citations